2018
DOI: 10.1371/journal.pone.0196349
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary convergence in the biosyntheses of the imidazole moieties of histidine and purines

Abstract: BackgroundThe imidazole group is an ubiquitous chemical motif present in several key types of biomolecules. It is a structural moiety of purines, and plays a central role in biological catalysis as part of the side-chain of histidine, the amino acid most frequently found in the catalytic site of enzymes. Histidine biosynthesis starts with both ATP and the pentose phosphoribosyl pyrophosphate (PRPP), which is also the precursor for the de novo synthesis of purines. These two anabolic pathways are also connected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 87 publications
1
33
0
Order By: Relevance
“…29 Furthermore, PRPP takes also part in histidine and purine biosynthesis and might have played a role in their RNA world-counterpart. 30 Moreover, a previous ab initio study reported by Sponer et al 31 Pictorial representation of nucleotide formation from PRPP and purine/pyrimidine bases: current biological pathway versus putative prebiotic hydrothermal conditions suggested from the present work. Current living forms exploit the enzymatic catalysis of phosphoribosyltransferases.…”
Section: Graphical Toc Entrymentioning
confidence: 50%
“…29 Furthermore, PRPP takes also part in histidine and purine biosynthesis and might have played a role in their RNA world-counterpart. 30 Moreover, a previous ab initio study reported by Sponer et al 31 Pictorial representation of nucleotide formation from PRPP and purine/pyrimidine bases: current biological pathway versus putative prebiotic hydrothermal conditions suggested from the present work. Current living forms exploit the enzymatic catalysis of phosphoribosyltransferases.…”
Section: Graphical Toc Entrymentioning
confidence: 50%
“…The purine synthesis pathway and its regulation are highly conserved in all eukaryotes from fungi to mammals (Agmon et al, ). Most probably, the last common ancestor had a pathway with the same structure that diversified into the now known three eukaryotic domains (Armenta‐Medina, Segovia, & Perez‐Rueda, ; Vázquez‐Salazar, Becerra, & Lazcano, ).…”
Section: Purine Metabolism In Eukaryotesmentioning
confidence: 99%
“…Most probably, the last common ancestor had a pathway with the same structure that diversified into the now known three eukaryotic domains (Armenta-Medina, Segovia, & Perez-Rueda, 2014;Vázquez-Salazar, Becerra, & Lazcano, 2018).…”
Section: Purine Metabolism In Eukaryotesmentioning
confidence: 99%
“…Both TrpF and TrpC are homologs to the HisF/HisA pair; although a prebiotic synthesis of tryptophan has been reported, it is likely that this amino acid has occurred later in evolution. Therefore, the HisF/HisA pair is more ancient than the TrpF and TrpC proteins, antiquity that is in agreement with the key catalytic role played by histidine in many extant enzymes [34].…”
Section: Hisa and Hisf Gene Elongationmentioning
confidence: 52%
“…HisA, like TrpF, catalyzes an Amadori rearrangement, i.e., the irreversible isomerization of an aminoaldose to an aminoketose [33]. The same chemical rearrangement is responsible for the imidazole ring closure by HisF [34]. HisA and HisF share the ability to bind PRFAR (N9-[(59-phosphoribulosyl)-formimino]-5-aminoimidazole-4-carboxamide-ribonucleotide): HisA catalyzes the formation of PRFAR, and HisF catalyzes an ammonia-dependent reaction in which PRFAR is converted to IGP and AICAR.…”
Section: Hisa and Hisf Gene Elongationmentioning
confidence: 99%